Technological alternatives for replacement cows in the Cauto Valley - Ben?tez, D.; Ricardo, Yanet; Viamontes, M. I.; Romero, A.; Guevara, O.; Torres, Verena; Miranda, M.; Guerra, J.; Olivera, C. (Cuban Journal of Agricultural Science, 2014)
The behavior of replacement cows was evaluated up to their first calving. The cows were from rearing systems, and they were of dualpurpose. Crossbred Zebu cows were used for the production of female calves, as well as simple yards, mating per season and the manipulation of the lactation of the calf as reproductive technologies. A rational grazing system was designed for the feeding of the herds. The female calves were weighed at birth and at weaning, and remained all the time together with the cow, except those applied the seasonal weaning. The weaning was performed abruptly at eight months of age. Besides the cows described, crossbred yearling cows were used. They were from farms with rearing system or dual purpose. The herd was organized into two groups with line grazing, the lead was given grass at full availability. The protein deficiencies were complemented with legume banks. In another work, with three breeds, it was evaluated the influence of the mating season on the behavior in the reproductive cycles and on the growth of the growing female calves, during the period between 1981 and 2004. In the alternatives evaluated, the productivity of the breeders was increased up to 148 kg of weaned liveweight per cow in reproduction. The weaning weight increased up to 165 kg, the heifers were incorporated to reproduction with 300 kg of liveweight. The age at first calving was reduced up to 32 months and the birth rate was considered adequate for efficient exploitations. The application of the validated technologies permitted creating capacities for the production of replacement cows from the rearing units and of milk breeds, on sustainable basis with high biological and economical efficiency. Key words: grazing, mating, productivity, lactation, sustainability.